rLj-RGD3 Suppresses the Growth of HeyA8 Cells in Nude Mice - Yuanyuan Zheng; Li Lv; Longda Yi; Rui Wu; Rong Xiao; Jihong Wang (Molecules, 2017)
In the previous study, rLj-RGD3, a recombinant toxin protein which contains three RGD motifs, was reported to not only inhibit the proliferation of an ovarian cancer cell line, HeyA8 cells, by inducing apoptosis, but also block their adhesion, migration and invasion processes. However, whether rLj-RGD3 could also suppress the tumor growth in HeyA8 xenografted mice has not been reported yet. In the present study, rLj-RGD3 was intraperitoneally injected in the nude mice bearing HeyA8 tumors. Compared with the control group (normal saline), rLj-RGD3 inhibited the tumor growth significantly in the HeyA8 xenografted mice in a dose-dependent manner without affecting their body weights. Based on the H&E, Hoechst 33258 and TUNEL staining assays, as well as western blot analysis, rLj-RGD3 reduced the weight and volume of the solid tumors, probably by disturbing the tissue structure, inducing apoptosis and suppressing the FAK/PI3K/AKT pathway. Most importantly, rLj-RGD3 was found to prolong the survival days of the ovarian tumor xenografted mice, which suggested rLj-RGD3 might act as an effective and safe drug to treat ovarian cancer patients.